Contribution of Self Confidence and Peer Conformity to Interpersonal Communication - Muhammad Riswan Rais; Marjohan Marjohan (RedWhite Press, 2020)
This research is motivated by the low ability of the students of MAN 1 Mandailing Natal in communicating well interpersonal. Self-confidence and peer conformity are factors that are thought to affect interpersonal communication. This study aims to describe: (1) self-confidence, peer conformity, and interpersonal communication, (2) the contribution of self-confidence to interpersonal communication, (3) the contribution of peer conformity to interpersonal communication, (4) the contribution of confidence and peer conformity. peers together on interpersonal communication. This research uses a descriptive correlational quantitative method. The study population was all students of MAN 1 Mandailing Natal, amounting to 1130 people, a sample of 295 people, who were selected by proportional random sampling technique. The instrument used was a Likert scale model. The data were analyzed using descriptive statistics, simple regression, and multiple regression. The research findings show that: (1) on average, students 'self-confidence is in the high category, (2) peer conformity is in the high category, (3) students' interpersonal communication is in the good category, (4) self-confidence contributes 47.8 % towards interpersonal communication, (5) peer conformity contributes to interpersonal communication by 19.2%, and (6) peer confidence and conformity together contribute to interpersonal communication by 49.5%